2003
DOI: 10.1097/01.tp.0000080069.61917.18
|View full text |Cite
|
Sign up to set email alerts
|

Graft protective effects of heme oxygenase 1 in mouse tracheal transplant-related obliterative bronchiolitis1

Abstract: HO-1 protein expression is increased in murine heterotopic airway rejection, and deficiency of HO-1 accelerates the development of the obliterative bronchiolitis-like lesion. IL-10 protein expression parallels expression of HO-1, suggesting that IL-10 may participate in the genesis of HO-1's effects on the inflammatory processes triggered by allotransplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…While pharmacologic induction of HO-1 did not alter rejection in this model (67), Song and coworkers recently demonstrated anti-inflammatory and antiapoptotic effects of exogeneous CO administration in a rat orthotopic lung transplantation model (68). More recently, Minamoto and colleagues demonstrated a protective role for HO-1 in a tracheal transplant model of BO (69).…”
Section: Bronchiolitis Obliterans/lung Transplantationmentioning
confidence: 83%
“…While pharmacologic induction of HO-1 did not alter rejection in this model (67), Song and coworkers recently demonstrated anti-inflammatory and antiapoptotic effects of exogeneous CO administration in a rat orthotopic lung transplantation model (68). More recently, Minamoto and colleagues demonstrated a protective role for HO-1 in a tracheal transplant model of BO (69).…”
Section: Bronchiolitis Obliterans/lung Transplantationmentioning
confidence: 83%
“…27 Our laboratory and others have shown that the integrity of the epithelium is critical in preventing the development of the OB-like lesion in the mouse tracheal transplant model. 13,28,29 Stabilization of the epithelium may prevent the formation of granulation tissue. There was less epithelial loss in the pirfenidonetreated group, although to a lesser degree than the reduction of intraluminal granulation tissue or fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…At this time, it is difficult to envision how seeding of epithelial cells could be performed in recipients of lung transplants, although the use of recipient stem cells may be promising for development of a similar treatment. A more plausible approach to prevent OB development would be protection of airway epithelial cells by activation of "protective genes," such as HO-1, 34 which may be capable of reducing local inflammation at the epithelial level in cases of allograft reactivity. This could be achieved by exposure of donor lung to carbon monoxide, a treatment shown to be effective in a rat lung transplantation model.…”
Section: Discussionmentioning
confidence: 99%